Arabic: The language of Muslimness in Cape Town - Sadan, Fatima (Linguistics, 2026)
This dissertation is a linguistic ethnography of Arabic language use among Muslims in Cape Town. The study seeks to understand how a group of Arabic learners experience and engage with Arabic as the language of Islam. The teaching of Arabic in South Africa has often been seen as problematic by researchers, many of whom have argued that students do not acquire communicative skills in these learning environments (Mall & Nieman 2002; Dawood 2008; Mohamed 1998, 1997). Such critiques conceive of language ability, or proficiency, in terms of four skills, namely, speaking, reading, writing, and comprehension. These four language skills have been deemed lacking among many Arabic language learners. Even though these researchers have acknowledged that Arabic is a religious language, they have tended to overlook the myriad ways in which Arabic ‘lives' in the complex semiotic repertoires of Capetonian Muslims who learn the language for religious purposes. This study shows that Arabic language practices and the ideologies surrounding the language are deeply intertwined with participants' spiritual/religious ideologies about Muslimness. The group of Arabic learners who are at the centre of the research spend hours vocalising Arabic sounds when reciting Quran, performing prayers, and reading religious texts. In other words, their daily religious practices, which form part of their everyday lives, are saturated with Arabic sounds and script. Moreover, they are visually and somatically engaged in writing Arabic script when doing calligraphy and copying Arabic texts by hand. Thus, this study asks, how do Muslim Arabic learners in Cape Town meaningfully engage with Arabic amidst their perceived ‘lack' of communicative language abilities? In what way do they make meaning with Arabic in their daily practices, and in what ways is the materiality of language involved therein? This study included ten participants: eight were in their twenties, and two were in their fifties. Through in-depth interviews and participant observation, this ethnographic study examines how Muslim learners experience Arabic as the language of Islam; how the characterisation of Arabic as a sacred language opens up different pathways of meaning-making; and how Muslim learners experience the (sonic and written) materiality of Arabic in their daily lives. The data were analysed using the constant comparative method (Merriam & Grenier, 2019: 43) alongside MacLure's (2013: 661) approach of attuning to “glowing” data – moments in the data that evoke affective or conceptual resonance. The analysis was informed by theories of language materiality (Cavanaugh & Shankar, 2017: 2) and the aesthetics of language (Jakobson, 1960: 356). These frameworks foreground three key concepts – ideologies, indexicality, and iconicity – which shaped the interpretation of the data. This dissertation argues that Muslim learners in Cape Town meaningfully engage with Arabic as a sacred language by prioritising the aesthetic and affective dimensions of language (Jakobson 1960; Besnier 1990), and in so doing, emphasise the aural and visual materiality of Arabic in their cultivation of Muslimness.